Extending Amdahl's Law for the Cloud Computing Era. - Diaz-del-Rio, Fernando; Salmeron-Garcia, Javier; Sevillano, Jose Luis (Computer (00189162), 2016)
By extending Amdahl's law, software developers can weigh the pros and cons of moving their applications to the cloud.